FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNA UNTUK BERTAHAN PADA BLACKBERRY SMARTPHONES - Cahyaningtyas Ria Uripi; Wisnu Wijayanto (Universitas Amikom Purwokerto, 2015)
Research about customer loyalty on Blackberry users is interesting, because competition in market of smartphones is powerfull. The purpose of this study was analyzed the effect of trust, customer satisfaction and switching cost on customer loyalty of Blackberry Smartphones users in Purwokerto. The sample of this study was 133 respondents. The analytical tool used in this study is Structural Equation Modeling (SEM) with Amos 16.0 program. The results of this study indicate that trust, customer satisfaction and switching cost effect on customer loyalty. Thus, Blackberry Smartphones needs to provide the highest priority on switching cost, because it would strengthen customer loyalty. Keywords : blackberry, android.